2018
DOI: 10.1111/all.13530
|View full text |Cite
|
Sign up to set email alerts
|

Association of mast cells with clinical, endoscopic, and histologic findings in adults with eosinophilic esophagitis

Abstract: To the Editor, Eosinophilic esophagitis (EoE) presents with diverse features which can differ between children and adults, as well as among adults, but eosinophils alone do not account for this heterogeneity. 1,2 Mast cells are involved in EoE pathogenesis, are highly increased

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 9 publications
(11 reference statements)
2
8
0
Order By: Relevance
“…Consistent with findings in EG tissue, as well as previously published findings, mast cells and eosinophils were significantly increased to a similar extent compared with nondiseased esophageal tissue ( Figure 1, E and F, and refs. [12][13][14][15][16]. These data demonstrate that both eosinophils and mast cells are markedly and proportionally elevated in both EG and EoE patient tissue and support our flow cytometry-based approach to quantitatively assess immune cells in fresh human tissue.…”
Section: Eg and Eoe Tissues From Patients Have Elevated Numbers Of Bosupporting
confidence: 72%
See 1 more Smart Citation
“…Consistent with findings in EG tissue, as well as previously published findings, mast cells and eosinophils were significantly increased to a similar extent compared with nondiseased esophageal tissue ( Figure 1, E and F, and refs. [12][13][14][15][16]. These data demonstrate that both eosinophils and mast cells are markedly and proportionally elevated in both EG and EoE patient tissue and support our flow cytometry-based approach to quantitatively assess immune cells in fresh human tissue.…”
Section: Eg and Eoe Tissues From Patients Have Elevated Numbers Of Bosupporting
confidence: 72%
“…A role for mast cells driving EGID pathogenesis is supported by the association of EGIDs with atopic diseases, the effectiveness of dietary therapy, and induction of immediate-and late-phase allergic reactions upon mast cell activation via high-affinity IgE receptors (12,13,32). Earlier studies in EoE have shown that mast cells are elevated and correlate with clinical symptoms as well as endoscopic and histologic findings (14). To better define the role of mast cells and eosinophils in EG, we used flow cytometry to characterize fresh gastric tissue from EG and nondiseased subjects at the single-cell level and found that both eosinophils and mast cells were selectively and significantly increased in EG gastric tissue.…”
Section: Discussionmentioning
confidence: 99%
“…This study was a secondary analysis of data and biospecimens collected during a prospective cohort study and was approved by the UNC IRB (#15-0163). Details of the parent study have been previously described [29][30][31][32][33], and subjects who participated provided informed consent for future use of banked biopsy samples. In brief, adults (age 18-80) who were undergoing a clinically indicated upper endoscopy for upper gastrointestinal (GI) symptoms (dysphagia, heartburn, chest pain or abdominal pain) were enrolled.…”
Section: Methodsmentioning
confidence: 99%
“…11 Immunohistochemical staining of esophageal mucosal biopsies from EoE patients for mast cell tryptase regularly reveals increased numbers of intact and degranulated mast cells, often to the point that mast cell density (cells/mm 2 ) exceeds eosinophil density. 12,13 In addition, recent studies in children with EoE suggest that mast cells play an eosinophil-independent role in causing the clinical manifestations of the disease. 14 Like eosinophils, mast cells produce many pro-inflammatory cytokines and toxic molecules capable of damaging neurons.…”
Section: Introductionmentioning
confidence: 99%